Social Studies Material Design Based on Cultural Literacy as a Systemic Program for Developing Social Skills Competencies - Deny Setiawan; Tappil Rambe; Lukitaningsih Lukitaningsih (RIRAI Publisher, 2023)
The 21st century life skills are seen as urgent in connection with globalization that brings change and paradox that demands students' competencies to be equipped with a number of social skills so that they can be competitive in the global era. To meet these competencies, it is necessary to designed the 21st century social skills systemic programs in the scope of higher education. This study aims to design social studies based cultural literacy material to develop student social skills competencies. The research method used is the R&D method by following the Borg & Gall procedures. The research subjects involved: lecturers of courses; students as subjects for limited group trials; and four experts who have social studies expert criteria. The instrument used was the Social Studies learning material design questionnaire which was validated by experts and analyzed using the average percentage of scores. Data analysis was also carried out on the results of observations related to student social skills competencies through qualitative descriptive analysis techniques. Observation of student competencies is carried out both during the learning process takes place in the classroom and in project activities outside the classroom. The results showed that the design of social studies learning material based on cultural literacy was declared valid and suitable for use. The results also show that learning material designs can develop student social skills competencies which include aspects: Social interaction skills, effective communication skills, skills in building teams, and skills in problem solving.